Model for the prediction of separation profile of oil-in-water emulsion - Aleem, W. (Taylor and Francis Inc., 2018)
This paper proposed a model that explains the separation mechanism of oil-in-water emulsion taking into account both creaming and coalescence processes. Oil-in-water emulsion separation experiments were performed in a batch separator using kerosene and distilled water. The predictions of the proposed model agreed well with the experimental results as well as previously published experimental data. The comparison between the proposed model and the previously published model showed that the proposed model has higher accuracy in predicting the separation profile of oil-in-water emulsion, with an accuracy of within 10. Thus the proposed model gives better representation of the oil-in-water emulsion separation process. Â© 2017 Taylor & Francis.